Material flow cost accounting (MFCA) for the circular economy: An empirical study of the triadic relationship between MFCA, environmental performance, and the economic performance of Japanese companies. (1st February 2022) - Nishitani, Kimitaka; Kokubu, Katsuhiko; Wu, Qi; Kitada, Hirotsugu; Guenther, Edeltraud; Guenther, Thomas
Abstract: The purpose of this study is to address the question of whether material flow cost accounting (MFCA) can contribute to the circular economy. Because MFCA is an environmental management accounting tool that simultaneously assesses company material and financial flows, it is expected to contribute to the circular economy by assisting companies to achieve both environmental and economic goals through resource efficiency. In short, the expected linkages between MFCA, company environmental and economic goals, and the circular economy are inputs, outputs, and outcomes. However, there is a lack of consensus regarding its potential, perhaps because of the scarcity of studies, with most being models and case studies without readily generalizable results. To address this gap, we analyze the triadic relationship between MFCA, environmental performance, and economic performance using a two-stage regression of data from Japanese listed companies. The main findings are as follows. Companies that implement MFCA more proactively are more likely to improve their environmental performance in terms of energy consumption, CO2 emissions, and waste produced. In turn, those that improve their environmental performance are also more likely to improve their productivity, while those that specifically improve environmental performance in terms of waste produced are also more likely to increase in profitability. Consequently, because MFCA can improve several aspects of environmental performance by saving resources, it can improve productivity by improving a range of environmental performance indicators. In particular, MFCA can improve company productivity and thereby profit, at least by reducing the amount of waste produced. This supports the view that MFCA is an effective tool to contribute to the circular economy. Highlights: We clarify the role of material flow cost accounting (MFCA) in a circular economy. We analyze the triad of MFCA, environmental performance, and economic performance. MFCA improves productivity by improving several environmental performance measures. MFCA improves productivity and thereby profit, at least by reducing waste produced. MFCA is an effective tool for a circular economy via inputs, outputs, and outcomes.